Single Nucleotide Polymorphisms (SNPs) Of Adiponectin Gene And Its Association With Serum Adiponectin Concentration And Metabolic Syndrome Risk Factors Among Malay Adults - Isa, Nur Firdaus (2011)
Metabolic syndrome is a cluster of risk factors that include central obesity, hypertriglyceridaemia, reduced HDL cholesterol, hypertension, and hyperglycemia. Accumulating evidences support the hypothesis that hypoadiponectinemia, a type of adipokine, confer increased risk for metabolic diseases. Of interest, some of the common polymorphisms in the promoter region, exon and intron 2 of the human adiponectin gene are associated with risk factors of metabolic syndrome. The present study aims to investigate the association of several single nucleotide polymorphisms in the adiponectin gene with serum adiponectin concentration and metabolic syndrome risk factors among Malay adults.